The Influence of INSTAD Learning Strategies Toward Students High Order Thingking Skills In Studying Biology - Evi Nur Qolbaini; Puguh Karyanto; Bowo Sugiyarto (Universitas Sebelas Maret, 2012)
This research aims to ascertain the influence of INSTAD learning strategies towards high order thinking in biology.This research was considered as a research, hence quantitative approach was used in this research.. The research design was pretest-posttest randomized subject control group using two classes which was taken by cluster ramdom sampling. The data was collected through four kinds of method, namely documentation, questionnaire, test, and observation. Documentation method was used to obtain the cognitive score. The data of high order thinking was taken by using test method. Questionnaire was used to assess student’s response to INSTAD and thinking skill, while implementation of INSTAD was examined through observation. The overall data were analyzed by using anacova.The conclution was that, the application of INSTAD strategy gave unsignificant to high order thinking skill in learning biology. Key Words: INSTAD learning strategies, HOTS